Glomalin‐related soil protein distributions in the wetlands of the Liaohe Delta, Northeast China: Implications for carbon sequestration and mineral weathering of coastal wetlands. (19th November 2019) - Pei, Lixin; Ye, Siyuan; Yuan, Hongming; Pei, Shaofeng; Xie, Shucheng; Wang, Jin
Abstract: Arbuscular mycorrhizal fungi (AMF) is presumably to be associated with carbon sequestration and nutrient acquisition through mineral weathering in wetland ecosystems. However, information on AMF‐carbon‐weathering interactions is limited. Grain size, concentrations of nutrients, and the major components of 304 surface sediment samples and glomalin‐related soil protein (GRSP) in 133 surface sediment samples were analyzed in various environments, including the upper delta plain wetlands (UDPW) and its adjacent shallow sea wetlands (SSW), to evaluate the relationship among the GRSP, carbon content, nutrients, and chemical index of alteration (CIA) in the wetlands of the Liaohe Delta (LHD). The concentrations of GRSP in surface sediments ranged between 0.11 and 11.31 mg g −1, with an average of 2.30 ± 0.17 mg g −1, and were significantly affected by the vegetation types. The ratios of organic carbon in GRSP (GRSP‐C) to soil organic carbon (SOC) varied from 0.71% to 25.34%, with an average of 10.34% ± 0.52%, indicating that the GRSP was an important carbon pool in sediments, and the carbon dynamics in these wetlands were closely related to human activities. Moreover, the CIA values ranged from 18.97 to 68.75, and were significantly higher in the UDPW than in the SSW ( p < 0.05), and were significantly correlated with the concentrations of GRSP ( r 2 = 0.22 [ r = 0.43], p < 0.01). Meanwhile, both the CIA and GRSP were significantly correlated with SOC, Total Nitrogen, and Fe ( r 2 > 0.17 [ r > 0.41], p < 0.01). The results indicate that AMF excursions in wetland ecosystems enhance carbon sequestration and mineral weathering, and in turn they alter retention of at least some nutrients.